Багатофакторна автентифікація в системі контролю доступу з використанням сенсорної мережі - Афанасьев, Ю. В. (ХНУРЕ, 2020)
Ensuring access control to facilities based on tlie use ot telecommunication systems and networks is an urgent task. This problem is solved by finding effective ways to build access control systems. The paper studies the possibility of building an access control system based on one-factor and multi-factor authentication. A version of the hardware and software system implementation is proposed. For various system configuration options, the system availability time has been experimentally determined.